Sorting it out: AP-2 and alternate clathrin adaptors in endocytic cargo selection - Traub, Linton M. (The Rockefeller University Press, 2003)
The AP-2 adaptor complex is widely viewed as a linchpin molecule in clathrin-mediated endocytosis, simultaneously binding both clathrin and receptors. This dual interaction couples cargo capture with clathrin coat assembly, but it has now been discovered that the association with cargo is tightly regulated. Remarkably, AP-2 is not obligatory for all clathrin-mediated uptake, and several alternate adaptors appear to perform similar sorting and assembly functions at the clathrin bud site.